Usborne: Big puzzle pad - Robson, Kirsteen (London, Usborne Publishing Ltd, 2021)
A big, colourful book crammed full of word, number, picture and logic puzzles. Each puzzle-packed page in this book has a different theme, from robots and space to Ancient Egypt and the Wild West, and the back of each sheet features another puzzle, with outline illustrations to complete and colour in.